Update on the ultrasound diagnosis of deep pelvic endometriosis. (February 2017) - Reid, Shannon; Condous, George
Abstract: Transvaginal ultrasound (TVU) is evolving as an essential tool in the work up for women with pelvic pain and suspected endometriosis. Several studies have demonstrated the accuracy and reliability of TVU for the diagnosis of pelvic deep infiltrating endometriosis and pouch of Douglas obliteration. Assessment of the anterior pelvic compartment for urinary DIE and utero-vesical adhesions should also be considered in the TVU examination for women with pelvic/pain suspected endometriosis. In addition, the use of ultrasound markers such as ovarian endometriomas and ovarian immobility may also aid in the assessment for disease severity. The ability to map disease location and extent pre-operatively allows for appropriate triaging, surgical planning and patient counselling, and in turn, improved care for women with severe endometriosis. This update focuses on the most recent advances surrounding the use of TVU for the prediction of endometriosis location and severity.